The Effectiveness of the Word Square Learning Model on Reading Ability: A Quasi-Experimental Study of Fourth-Grade Students in Indonesian Language Instruction - Shaltina, Ayu Amalia; Herlina, Herlina; Lapasere, Sisriawan; Aqil, Muhammad; Putriwanti, Putriwanti; Surahman, Surahman (Journal of Innovation and Research in Primary Education, 2026)
Reading ability constitutes a fundamental skill essential for academic success, yet many elementary students experience persistent difficulties in developing adequate reading competencies. The Word Square model, a game-based puzzle intervention, offers a promising approach to enhance reading instruction through active word recognition and contextual learning. This study investigated the effectiveness of the Word Square learning model on reading ability among fourth-grade elementary students in Indonesian language instruction. A quasi-experimental design with nonequivalent control groups was employed, involving 44 students divided into experimental (n=22) and control (n=22) groups. The experimental group received Word Square instruction while the control group participated in conventional teaching. Reading ability was assessed through pretest and posttest measurements. Data were analyzed using descriptive statistics, Shapiro-Wilk normality test, Levene’s homogeneity test, independent samples t-test, and normalized gain (N-gain) analysis. The experimental group achieved significantly higher posttest scores (M=89.64) compared to the control group (M=70.86), with t=13.636, p<0.001. The N-gain coefficient of 0.7325 indicated high effectiveness, demonstrating substantial improvement relative to students’ growth potential. The Word Square learning model significantly enhances reading ability among fourth-grade students, providing robust empirical support for game-based, student-centered pedagogical approaches in elementary literacy instruction. These findings offer practical implications for educators seeking evidence-based strategies to improve reading outcomes.